2019
DOI: 10.3389/fpubh.2019.00277
|View full text |Cite
|
Sign up to set email alerts
|

Jakartans' Perceptions of Health Care Services

Abstract: Health Care Services (HCSs) should implement ongoing innovation and continuously improve their quality. However, in evaluating the quality of HCSs, too little attention has been given to the experience of the users concerning the acquired services. This study focused on how the community values the current services in order to improve HCSs in Indonesia, especially in Jakarta. Four focus group discussions were conducted among 45 community members in the Grogol Petamburan sub-district, in Jakarta. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Indonesia’s insurance health system allows women to choose their health facility (public or private), provided that the facility has cooperated with the insurance company to accept insured patients and most private facilities do. 44 45 Preferences for private facilities due to reputation, especially in urban areas, 46 may translate in to higher proportions of women giving birth at private instead of public facilities. Unlike the trend on facility-based births; however, the CSRs were higher across time in public compared with private facilities, except in 2017, when the rates are similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia’s insurance health system allows women to choose their health facility (public or private), provided that the facility has cooperated with the insurance company to accept insured patients and most private facilities do. 44 45 Preferences for private facilities due to reputation, especially in urban areas, 46 may translate in to higher proportions of women giving birth at private instead of public facilities. Unlike the trend on facility-based births; however, the CSRs were higher across time in public compared with private facilities, except in 2017, when the rates are similar.…”
Section: Discussionmentioning
confidence: 99%
“… 25 61 67 68 71 Furthermore, women living in urban areas with financial capabilities and not relying on JKN often bypass this system to give birth at private clinics. 46 …”
Section: Introductionmentioning
confidence: 99%
“…The present study is a follow-up of our previous studies (Sokang et al, 2019c;Sokang, Westmaas, & Kok, 2019b;Sokang et al, 2019a), which found differences between the approach of health providers in promoting health and the values that are considered important by the people of Jakarta, Indonesia (Sokang et al, 2019c(Sokang et al, , 2019a. As a result, the community members preferred self-and traditional treatments, and only came to health services when the disease becomes more severe (Sokang et al, 2019b(Sokang et al, , 2019c. Therefore, the health providers proposed to involve community members, such as health cadres/ volunteers, key leaders, and religious leaders to promote health in the community (Sokang et al, 2019b).…”
Section: Introductionmentioning
confidence: 73%
“…This might be related to the community's perception of the CHCs as a place to get treatment (Sokang, Westmaas, & Kok, 2019c). At the same time, the lack of evaluation on the CHCs' performance makes it difficult for policy makers and health promoters to understand to what extent the CHCs' health promotion efforts have succeeded or failed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation